Pengaruh Harga, Kualitas Pelayanan, Dan Word of mouth Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada PT. Shafira Tour & Travel Umroh Dan Haji Plus Cabang Probolinggo - Ningsih, Bunaya Wahyu; Suharsono, Judi; Junaidi, Junaidi (Universitas Panca Marga, 2024)
The purpose of the study is to determine the direct and indirect influence on price variables, service quality, word of mouth, consumer satisfaction and consumer loyalty. The sample taken in this study was 50 respondents. The data collection technique in this study uses the questionnaire method. The data analysis technique in this study uses the Research Instrument Test (Validity Test, Reliability Test), Model Accuracy Test (R-Square, Hypothesis Test) with the help of SMART PLS 4. The results of this study show that price variables, service quality, word of mouth, and consumer satisfaction partially have a positive and significant effect on consumer loyalty. As well as price variables, service quality and word of mouth partially have a positive and significant effect indirectly on consumer loyalty through consumer satisfaction.